The Impact of Crypto Currency Mining on Academic Performance Among Students Of Higher Institutions In Nigeria - Jajere , Bello Muhammad; Audu, Mohammed Yunusa; Muhammad, Adamu Abubakar (CV Media Inti Teknologi, 2024)
This study aims to evaluate how mining activities affect academic outcomes, the relationship between time spent on mining and academic performance, and the key influencing factors. In addition, it explores students' perceptions and offers strategies to mitigate negative impacts. A quantitative approach was used, with data collected from 197 students through an online questionnaire. The survey includes demographics, mining activities, learning habits, academic performance, and perceptions. The findings reveal a nuanced relationship: 48.7% of students admit some mining influence on their academics, while 51.8% disagree. The difference in discipline and time management is significant, as some students manage mining and academics well, while others struggle. Stress and time management issues are prevalent, with 39.6% reporting increased stress. In addition, 56.6% of students expressed a need for institutional support. Based on the results of this study, it can be concluded that the impact of cryptocurrency mining on academic performance varies based on individual factors and suggests various actions such as time management workshops, academic counseling, specialized learning environments, stress management programs, resource allocation, peer support groups, flexible learning options, performance monitoring, awareness campaigns, and collaboration with technology companies.